Pengaruh Good Corporate Governance Terhadap Kualitas Laba Pada Perusahaan Real Estate dan Property - Vika Fitranita; Isma Coryanata (Jurnal Akuntansi, 2018)
This study aims to analyze the effect of corporate governance on the quality of study earnings in real estate and property companies listed on the Indonesia Stock Exchange (IDX) in 2012-2017. In this study, Good Corporate Governance is analyzed as a factor that can encourage companies to have good earnings quality. This study belongs to the type of descriptive research verification of causality. The population in this study are real estate and property companies listed on the Indonesia Stock Exchange (IDX) in 2012-2017 using the purposive sampling method. The type of data collected and used in this study is secondary data with a method of collecting data through documentation and literature studies. The data analysis method used is simple linear regression analysis that has met the testing of classical assumptions. The results of this study indicate that Good Corporate Governance has no effect on earnings quality because the application of Good Corporate Governance (GCG) in companies in Indonesia has not really been used as a tool to minimize information asymmetry between owners and management, but solely to comply with regulations and conditions that apply only.Key words: Good Coporate Governance, kualitas laba.